PENGARUH DUKUNGAN MANAJEMEN PUNCAK, KETERLIBATAN PENGGUNA, FORMALISASI PENGEMBANGAN SISTEM, PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Studi di Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah Kota Surakarta) - Mentari Risnanti, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2019)
The purpose of this research is to analyze the significance of the influence of top management support, user engagement, formalisasi systems development as well as training and education of accounting information system on performance of the Agency's Revenue Financial and assets management Area of the city of Surakarta. The research results obtained conclusions that: 1) there is a significant positive influence on the support of top management on performance information system accounting. 2) there is a significant positive influence on user engagement on performance of accounting information system on Financial management of Income and assets of the regional city of Surakarta. 3) there is a significant positive influence on the development of formalisasi system on performance of accounting information system on Financial management of Income and assets of the regional city of Surakarta. 4) there is a significant positive influence on training and education on performance system of accounting information on Income and assets financial management Area of the city of Surakarta. Keywords: top management support, user engagement. formalisasi systems development, training and education, the accounting information system performance.